2010
DOI: 10.1186/1471-2407-10-506
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling in canine osteosarcoma: identification of biomarkers and pathways associated with outcome

Abstract: BackgroundOsteosarcoma (OSA) spontaneously arises in the appendicular skeleton of large breed dogs and shares many physiological and molecular biological characteristics with human OSA. The standard treatment for OSA in both species is amputation or limb-sparing surgery, followed by chemotherapy. Unfortunately, OSA is an aggressive cancer with a high metastatic rate. Characterization of OSA with regard to its metastatic potential and chemotherapeutic resistance will improve both prognostic capabilities and tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 61 publications
3
61
1
Order By: Relevance
“…Moreover, our finding is also in agreement with previous gene expression profiling studies using both in vitro and in vivo models that identified both cytoskeletonremodeling and focal adhesion as metastatic pathways in OS. [32][33][34][35] Consistent with our pathway analyses, OS cells with SATB2 knockdown were characterized by morphological differences in the actin cytoskeleton. Sh-SATB2 cells were more elongated with increased stress fiber formation.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, our finding is also in agreement with previous gene expression profiling studies using both in vitro and in vivo models that identified both cytoskeletonremodeling and focal adhesion as metastatic pathways in OS. [32][33][34][35] Consistent with our pathway analyses, OS cells with SATB2 knockdown were characterized by morphological differences in the actin cytoskeleton. Sh-SATB2 cells were more elongated with increased stress fiber formation.…”
Section: Discussionsupporting
confidence: 87%
“…Efficiency analysis identified the J5 test (123) as the most internally consistent test (compared to fold-change, the D1 test, the t-test, and random feature selection) after z-transform for the first two comparisons and after mean normalization for the third comparison. The J5 test is especially useful for datasets with a small number of replicates and may reduce the number of false positives generated through other analytical methods (19,123), and this test has previously been used to analyze microarray data from diverse sources (18,25,42,106,118,128,131,144). Missing values were imputed using k-nearest neighbors.…”
Section: Methodsmentioning
confidence: 99%
“…A number of 51 transcripts were found to be differentially expressed and hierarchical clustering, validated by reverse transcriptase polymerase chain reaction (RT-PCR) analysis, revealed that four genes, namely ANKRRD17, MGST1, MRPS31, and NCOR1, were overexpressed in the short survival group. Expression profiling following the same technique identified both biomarkers and pathways associated with the clinical outcome 102 in dogs that View Article Online responded poorly to chemotherapy and dogs that responded well, as defined by the disease-free intervals (o100 days and 4300 days). Differentially expressed genes related to the hedgehog signalling pathway, such as HHIP, were found to be upregulated in the poor responder cohort.…”
Section: Osteosarcomasmentioning
confidence: 99%